Peranan Perguruan Tinggi di Semarang dalam Pelestarian Wayang Orang Ngesti Pandowo - Dhanang Respati Puguh; Mahendra Pudji Utama; Rabith Jihan Amaruli (Jurnal Sejarah Citra Lekha, 2019)
Ngesti Pandowo is a wayang orang group founded in Madiun, East Java on July 1, 1937. Since 1954, this community has been settled in Semarang and reached its heyday in the 1950-1970 and become the City’s icon. In the late 1970s, Ngesti Pandowo suffered a continuing setback. It raised the concern and attention of a number of groups including the government, universities in Semarang, and the business parties to maintain its sustainability. This article is focused on the discussion of the efforts of the universities in Semarang to preserve Ngesti Pandowo. This article used historical methods, oral history, and literature study. The results show that universities in Semarang had played an important role in preserving Ngesti Pandowo through various activities, namely: art appreciation, management development, player support, and technology utilization.